Ferramentas de melhoria contínua aplicadas em uma oficina de manutenção hidráulica situada em Parauapebas-PA - VIEIRA, Emanoel Laurentino (2021)
The substantial increase in vehicles and machines fleet with hydraulic system has raised the demand for services with this purpose in recent years, so it is of paramount importance that companies in this field of industry to act efficiently and with quality services seeking to solve customer problems. This work presents a case study referring to the implementation of continuous improvement in a small or medium-sized company in the field of hydraulic maintenance services. Some specific points within the organization were analyzed and, in some cases, a few basic quality tools were used viewing improvements for each sector. The industrial layout is one of the evident characteristics in an organization and from it is able to observe how the company works, how the flow of products and maintenance occurs, including detecting existing failures in the entire process. The Ishikawa Diagram was used to analyze the main causes of failure inside the organization, also the main negative results that failures generate, and from this point it was possible to carry out the action plan through the 5W2H method, using the PDCA cycle. A new layout model was proposed, which has become fundamental for an internal organization of the company and improvement of the flow of materials and people within the Hydraulic Workshop, minimizing the lead-time of services.